2022
DOI: 10.1097/iae.0000000000003281
|View full text |Cite
|
Sign up to set email alerts
|

Peripapillary Microvasculature of the Retina and Choriocapillaris in Uninvolved Fellow Eyes of Unilateral Retinal Vein Occlusion Patients

Abstract: Purpose: To investigate peripapillary microvascularity of the retina and choriocapillaris in uninvolved fellow eyes of patients with branch retinal vein occlusion (RVO) compared with that of healthy controls. Methods: Peripapillary optical coherence tomography angiography bilateral eye scans of 46 patients with unilateral RVO and 46 age-matched control eyes were reviewed. Microvascular density in radial peripapillary capillary plexus (RPCP), superficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…For example, ischemic CRVO fellow eyes were associated with significantly decreased retinal VFD, increased retinal thickness and volume, increased LMCV-VFD, and decreased CVI compared to healthy controls. These findings align with previous research by Park et al, 10 who also reported microvascular impairment in the retina and choroid of RVO fellow eyes. Collectively, these results lend support to the hypothesis that RVO is not solely a localized ocular event but may instead be indicative of broader systemic vascular changes affecting both eyes.…”
Section: Discussionsupporting
confidence: 93%
“…For example, ischemic CRVO fellow eyes were associated with significantly decreased retinal VFD, increased retinal thickness and volume, increased LMCV-VFD, and decreased CVI compared to healthy controls. These findings align with previous research by Park et al, 10 who also reported microvascular impairment in the retina and choroid of RVO fellow eyes. Collectively, these results lend support to the hypothesis that RVO is not solely a localized ocular event but may instead be indicative of broader systemic vascular changes affecting both eyes.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased choriocapillaris density in the macular region or peripapillary region has been reported in RVO eyes and fellow eyes in recent years ( 12 , 14 , 28 , 29 ). Some researchers suggested that the decrease of choriocapillaris density in the macular region was caused by hyperexpression of VEGF ( 30 ) while Aribas and associates believed choriocapillaris drop out in the macular region could be the pressure effect of the choroidal congestion ( 12 ).…”
Section: Discussionmentioning
confidence: 86%
“…As for the decrease of peripapillary choriocapillaris density, the vascular theory has been proposed by researchers ( 22 , 31 ) which suggested that the disturbance of peripapillary blood circulation would eventually lead to glaucoma. In a most recent study by Park and associates, the proportion of signal voids in the peripapillary choroid layer was larger in uninvolved fellow eyes of BRVO patients than in control eyes ( 29 ). The etiology of decreased peripapillary choroid flow has not been well elucidated, but the author suggested that the decreased choroid flow represented pathogenic circumstances, which made the eye more susceptible to RVO.…”
Section: Discussionmentioning
confidence: 95%